THE EFFECTIVENESS OF FLIPBOOK INTEGRATING TRI KAYA PARISUDHA TO ENHANCE STUDENTS’ GLOBAL DIVERSITY CHARACTER - Ardiawan I Ketut Ngurah (El Midad, 2025)
This study aims to examine the effectiveness of the “Jati Diri dan Lingkungan Kuku” flipbook, infused with Tri Kaya Parisudha values, in enhancing students’ global diversity character. The research employed a quasi-experimental design with a post-test control group model. The subjects were fifth-grade elementary school students in Buleleng Regency, with the experimental group using a digital flipbook and the control group following conventional learning methods. Data were collected using a global diversity character questionnaire, which covers cognitive, affective, and behavioural aspects. Results of the independent samples t-test indicated a significant difference between the groups (t = 15.181, p < 0.05), and the calculated effect size (ES 4.86) demonstrated a high level of effectiveness. These findings confirm that the Tri Kaya Parisudha-based flipbook is not only effective in enhancing global diversity character but also promotes meaningful learning, active engagement, and greater motivation among elementary school students. Beyond its practical implications, this study contributes to the development of educational science by demonstrating the relevance of integrating local wisdom into digital learning media as an innovative approach to strengthening character education in the era of globalisation.